The Comparison of Innovative and Strategic Priorities of Small and Large Companies in Russian local production systems - Kuznetsova, Svetlana (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Industrial companies are the core of the national innovation system. However, large, medium and small enterprises differ significantly in their role in the innovation system, resource potential, strategic priorities and objectives. The paper focuses on a comparative analysis of the strategic priorities of innovative activities of Russian companies of different size. We have identified three types of companies: small innovative companies, large and medium-sized companies with a traditional business model, major innovation-driven companies with an integrated business model. Our analysis of the trajectories of small innovative firms located in Novosibirsk Scientific Center showed that the majority of the companies can be characterized either as spin-off firm or as specialized supplier. Spin-offs are newly established small firms, who have recently separated from the major research labs or parent companies. The typical behavior model for such companies is innovative entrepreneurship. Specialized suppliers are small companies that provide significant contributions to complex manufacturing systems in the form of equipment, parts, tools and software. Innovative objectives of such small companies deal with design and production of the specific elements required for large companies. Large and medium-sized companies with a traditional business model are characterized by the existing structure of commodity output and the supply chain. Characteristic type of innovative behavior for such companies includes incremental product and process innovations. Large innovation-oriented companies with an integrated business model have traditional production units and innovative units in their structure. Innovation priorities of major innovation-oriented companies with integrated business model are consistent with the hybrid model of behavior which combines the traditional model with an innovative entrepreneurship.